PENGARUH CITRA MEREK DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PADA CV PANYILEUKAN BANDUNG - Erick Ivan Gian; Ida Bagus Alit Ksama Putra; Ridha Rahim Allibani; Hendriady de Keizer H; Risna Haryati; Putri Dwi Novrina; Fitriani Fajar (Jurnal Ilmiah Magister Ilmu Administrasi, 2023)
This study aims to examine the effect of: (1) brand image and promotion on purchasing decisions, (2) brand image on purchasing decisions, (3) promotion on purchasing decisions. The research design used in this research is causal quantitative research. In this study, the research subjects were customers who shopped at CV Panyileukan and the objects of research were brand image, promotions and purchase decisions. The population taken in this study is all consumers who shop at CV Panyileukan which amounts to 60 customers. Data were collected by interviews, document recording and questionnaire methods, then analyzed by multiple regression analysis. The results showed that: (1) brand image and promotion had a significant effect on purchasing decisions, (2) brand image had a significant effect on purchasing decisions, (3) promotion had a significant effect on purchasing decisions.